Propiedades psicométricas de la prueba de apego adulto "Experiencias en relaciones cercanas-revisado" (Experiences in close relationships-revised, ECR-R) en población colombiana (2009)
ABSTRACT: The present research study the psychometric properties of the measure Experiences in Close Relationships Revised (ECR-R). The results showed that 15 items doesn’t have those properties to be considered inside the test, either because their symmetry, because they didn’t have a factorial load equal or superior to 0.4; by cause of they loaded on several factors or they were conceptually isolated from the scales on the test. The factor analyses exposed that the ECR-R has a three factors structure, which are assembled in two scales, anxiety and avoidance. The 16 and 17 items originally in the scale of anxiety, scored for the factor 2 which matches with avoidance; that is why they were moved to the other scaled. Each of these scales got acceptable coefficients of internal consistency (anxiety = 0.877; avoidance = 0.798) and the normative values were determinated also for each scale. This is how the instrument of evaluation of attachment in relationships is obtained; and even it keep the same topics in reference to the scales that are evaluated, is not equal to the old one because many of the items were eliminated, making of this Spanish version, a short one.